All rights reserved - Katsoulis, Gregory Scott (Harlequin Teen, 2017)
In a world where every word and gesture is copyrighted, patented or trademarked, one girl elects to remain silent rather than pay to speak, and her defiant and unexpected silence threatens to unravel the very fabric of society. Speth Jime is anxious to deliver her Last Day speech and celebrate her transition into adulthood. The moment she turns fifteen, Speth must pay for every word she speaks ("Sorry" is a flat ten dollars and a legal admission of guilt), for every nod ($0.99/sec), for every scream ($0.99/sec) and even every gesture of affection. She's been raised to know the consequences of falling into debt, and can't even begin to imagine the pain of having her eyes shocked for speaking words that she's unable to afford. But when Speth's friend Beecher commits suicide rather than work off his family's crippling debt, she can't express her shock and dismay without breaking her Last Day contract and sending her family into Collection. Backed into a corner, Speth finds a loophole: rather than read her speech - rather than say anything at all - she closes her mouth and vows never to speak again. Speth's unexpected defiance of tradition sparks a media frenzy, inspiring others to follow in her footsteps, and threatens to destroy her, her family and the entire city around them. -- From dust jacket.